2010
DOI: 10.1177/1934578x1000500425
|View full text |Cite
|
Sign up to set email alerts
|

Compositions and in vitro Anticancer activities of the Leaf and Fruit Oils of Litsea cubeba from Taiwan

Abstract: The leaf and fruit essential oils of Litsea cubeba, extracted by hydrodistillation, were assessed for anticancer activities. A total of 53 and 50 compounds were identified, respectively from the leaf and fruit oils, and their yields were 13.9 ± 0.09% and 4.0 ± 0.03%, v/w, of the oven-dried materials, respectively. The main compound in the leaf oil was 1,8-cineol, and in the fruit oil, citral. The fruit oil, but not that of the leaf, exhibited cytotoxic activity against human lung, liver and oral cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 14 publications
2
45
0
1
Order By: Relevance
“…The chemical composition of essential oils of L. cubeba varies according to habitat and tissue Ho et al 2010). The three enzyme products obtained from the mono-TPS of L. cubeba have previously been reported to be the components of the essential oils from different parts of L. cubeba (Lagalante and Montgomerys 2003;Marriacci et al 1994).…”
Section: Different Expression Patterns Of Lctps In Varies Tissuesmentioning
confidence: 98%
See 1 more Smart Citation
“…The chemical composition of essential oils of L. cubeba varies according to habitat and tissue Ho et al 2010). The three enzyme products obtained from the mono-TPS of L. cubeba have previously been reported to be the components of the essential oils from different parts of L. cubeba (Lagalante and Montgomerys 2003;Marriacci et al 1994).…”
Section: Different Expression Patterns Of Lctps In Varies Tissuesmentioning
confidence: 98%
“…Previous studies have shown that the essential oils of L. cubeba dispel rheumatism, detoxify, and have an analgetic effect, and the extracts from different tissues also showed remarkable antioxidant activity in comparison with α-tocopherol and ascorbic acid (Hwang et al 2005). The dominant components in the essential oils of L. cubeba are monoterpenes (Ho et al 2010). In this article, we report the isolation and functional characterization of three monoterpene synthase (mono-TPS) genes from L. cubeba: LcTPS1, LcTPS2, and LcTPS3.…”
Section: Introductionmentioning
confidence: 98%
“…Cytotoxicity against tumor cell lines of its extracts, epigenetic modifications of cancer oncogenes, and tumor suppressor genes were described. It was also reported that Radix Angelicae sinensis may be a potential source of glutathione S-transferase inhibitors and counteract multidrug resistance [2630]. One report described antiproliferative activity of Gentiana triflora root extract on cultured and implanted tumor cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…One report described antiproliferative activity of Gentiana triflora root extract on cultured and implanted tumor cells [29]. Fruit oils of Litsea cubeba from Taiwan exhibited cytotoxic activity against human lung, liver, and oral cancer cells in vitro [30, 31]. Galangin, flavonol present in Alpinia galanga rhizome, induced apoptosis of cancer cells [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…All parts of this plant emanate a pungent gingery odor [10]. Fruits of L. cubeba are spicy condiments, frequently used in the aboriginal cuisine of Taiwan [11].…”
Section: Introductionmentioning
confidence: 99%